French myotonic dystrophy families show expansion of a CTG repeat in complete linkage disequilibrium with an intragenic 1 kb insertion. Issue 1 (January 1994) - Lavedan, C; Hofmann-Radvanyi, H; Boileau, C; Bonaïti-Pellié, C; Savoy, D; Shelbourne, P; Duros, C; Rabes, J P; Dehaupas, I; Luce, S
Abstract : The molecular basis of myotonic dystrophy (DM) has been characterised. All DM mutations characterised to date appear as an unstable elongation of a fragment containing a tandem repeat of a CTG motif, which can be visualised in both EcoRI and BamHI digests. It has been shown that the fragment is polymorphic in the normal population. Another 1 kb insertion/deletion polymorphism located near the unstable CTG repeat region has been identified. The 1 kb insertion allele is present in all DM patients. These different polymorphic systems can be distinguished using cDNA25 and BamHI, because this enzyme cuts between the site of the 1 kb insertion and the CTG repeat. We thus haplotyped DM patients from 72 French families and clearly showed that all chromosomes (100%) with the DM mutation carried the 1 kb insertion as well. In addition to this association, we detected significant linkage disequilibrium between the DM locus and D19S63 for which allelic frequencies were different from other European populations. Our results in the French DM population are thus in agreement with the hypothesis that the CTG expansion occurred on one or a few ancestral chromosomes carrying the large 1 kb insertion allele.